Sensitive Reading The Pleasures of South Asian Literature in Translation (Edition 1) - Bronner, Yigal; Hallisey, Charles (University of California Press, 2022)
A free open access ebook is available upon publication. Learn more at www.luminosoa.org. What are the pleasures of reading translations of South Asian literature, and what does it take to enjoy a translated text? This volume provides opportunities to explore such questions by bringing together a whole set of new translations by David Shulman, noted scholar of South Asia. The translated selections come from a variety of Indian languages, genres, and periods, from the classical to the contemporary. The translations are accompanied by short essays written to help readers engage and enjoy them. Some of these essays provide background to enhance reading of the translation, whereas others model how to expand appreciation in comparative and broader ways. Together, the translations and the accompanying essays form an essential guide for people interested in literature and art from South Asia.